Gender differences in personal issues related stress among university student athletes / Eng Hoe Wee ... [et al.] - Wee, Eng Hoe; Kee, Kang Mea; Ong, Tah Fatt; Ler, Hui Yin; Cheng, Wei Fong; Tan Abdullah, Nadiah Diyana; Tan, Chee Hian (Universiti Teknologi MARA, 2021)
Student athletes have to balance numerous demands such as academic pursuit, training and competition, thus these could bring stress and challenges. This study examined personal issues as sources of stress experienced by university student athletes. A total of 273 student athletes (Males = 160, Females = 113; Age = 20.4 + 2.5 years) participated in this study. A 16-item questionnaire was adopted from the Organizational Stress Inventory developed by Fletcher and Hanton (2003). The inventory was divided into three sub-scales of 'nutrition', 'injury', and goals and expectations'. The results suggested that both male and female student athletes were stressed, in order of importance by 'nutrition', 'injury' and 'goal & expectation' respectively. Inferential statistics showed that there were no significant differences in 'nutrition', 'injury' sub-scales according to gender. However, for the 'goal and expectations' sub-scale, there was a statistically significant difference in 'unclear goals' and 'tension because of personal goals within the team' where male athletes demonstrated higher stress than female athletes. The findings are important to coaches and sport managers in addressing personal issues among athletes. More research is needed to include athletes from other educational institutions and from national sport associations.